Transforming Banking Experiences: The Effectiveness of Sharia Management in Boosting Customer Satisfaction in Makassar - ., Awaluddin; Saleh, Haeruddin (Journal of Ecohumanism, 2024)
The growth of the Islamic banking industry in Makassar has shown significant progress; however, a thorough analysis of the factors influencing customer loyalty is still needed. This study aims to analyze the impact of product innovation, service quality, and transaction security on customer satisfaction and loyalty in Islamic banks in Makassar. Structural Equation Modeling (SEM) using AMOS was applied to data collected from 400 Islamic bank customers. The results indicate that service quality (estimate 0.253, C.R. 3.229) and transaction security (estimate 1.581, C.R. 3.216) have a significant impact on customer satisfaction. Product innovation also significantly affects customer satisfaction (estimate 0.723, C.R. 6.484) but does not significantly influence loyalty (estimate 0.130, C.R. 0.545, P 0.693). Conversely, customer satisfaction significantly affects loyalty (estimate 0.234, C.R. 2.534, P 0.027). The implications of this study highlight the importance of improving service quality and transaction security to enhance customer satisfaction and loyalty. Islamic banks should continue to develop innovative products and provide ongoing education to customers to maintain and boost their loyalty. The growth of the Islamic banking industry in Makassar has shown significant progress; however, a thorough analysis of the factors influencing customer loyalty is still needed. This study aims to analyze the impact of product innovation, service quality, and transaction security on customer satisfaction and loyalty in Islamic banks in Makassar. Structural Equation Modeling (SEM) using AMOS was applied to data collected from 400 Islamic bank customers. The results indicate that service quality (estimate 0.253, C.R. 3.229) and transaction security (estimate 1.581, C.R. 3.216) have a significant impact on customer satisfaction. Product innovation also significantly affects customer satisfaction (estimate 0.723, C.R. 6.484) but does not significantly influence loyalty (estimate 0.130, C.R. 0.545, P 0.693). Conversely, customer satisfaction significantly affects loyalty (estimate 0.234, C.R. 2.534, P 0.027). The implications of this study highlight the importance of improving service quality and transaction security to enhance customer satisfaction and loyalty. Islamic banks should continue to develop innovative products and provide ongoing education to customers to maintain and boost their loyalty.